Pneumococcal genomics and evolution - van Tonder, A (2016)
Streptococcus pneumoniae (the “pneumococcus”) is a global pathogen responsible for nearly a million deaths each year in children under the age of five. The polysaccharide capsule or serotype is the primary pneumococcal virulence factor and is encoded by the cps locus. The introduction of pneumococcal conjugate vaccines has led to a significant reduction in the prevalence of invasive diseases caused by vaccine serotypes and a concomitant reduction of vaccine serotypes recovered from the nasopharynx of healthy children, although the overall rates of carriage have remained constant due to the replacement of vaccine serotypes with non-vaccine serotypes. The increasing numbers of genomes from large well-characterised pneumococcal datasets allows for key biological questions related to the pneumococcus, such as capsular diversity, to be examined in unprecedented detail. This thesis describes the application of genomics to investigating important aspects of pneumococcal biology including the pan-genome, cps locus diversity and genomic regions potentially associated with invasive disease. The first part of the thesis described a Bayesian decision model for estimating bacterial core genomes. This model was applied to genome datasets from five different bacterial species. The same model was later used to estimate core genomes for four different pneumococcal carriage datasets. These estimated core genomes were then compared and revealed a very small shared core genome of 303 genes. The results also highlighted the unexpected diversity of a pneumococcal dataset from Thailand. The second part of the thesis examined the diversity of the cps locus starting with serogroup 6 and in particular the recently described novel serotype 6E. This analysis revealed that the majority of what had previously been described as serotype 6B pneumococci were in fact serotype 6E and serological assays demonstrated that vaccine-induced serotype 6B antibodies were able to kill serotype 6E pneumococci. The analysis of cps loci was then extended to consider the diversity of 49 serotypes and included 5,405 genomes in the analyses. These analyses revealed several hybrid and putative novel serotypes. The final part of the thesis used a genome-wide association study to identify 89 candidate loci significantly associated with invasive disease. The results in this thesis showed that large numbers of genome sequences could provide a detailed insight into important aspects of pneumococcal biology.